2010
DOI: 10.1016/j.joca.2010.03.014
|View full text |Cite
|
Sign up to set email alerts
|

The infrapatellar fat pad should be considered as an active osteoarthritic joint tissue: a narrative review

Abstract: These data are consistent with the hypothesis that the IPFP is an osteoarthritic joint tissue capable of modulating inflammatory and destructive responses in knee-OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
355
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(367 citation statements)
references
References 73 publications
(85 reference statements)
9
355
0
3
Order By: Relevance
“…It has been shown that an increase in signal intensity on fluid-sensitive fat-saturated sequences, representing an increase in tissue fluid referred to as edema, is sensitive in the acute phase of the disease [4,5,45]. More recently, it has been suggested that the infrapatellar fat pad also plays a relevant role in the development of OA [1][2][3]. OA is a disease with multifactorial pathophysiology, including inflammatory processes, modulated by mediators, some of which ultimately accelerate cartilage degeneration [46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that an increase in signal intensity on fluid-sensitive fat-saturated sequences, representing an increase in tissue fluid referred to as edema, is sensitive in the acute phase of the disease [4,5,45]. More recently, it has been suggested that the infrapatellar fat pad also plays a relevant role in the development of OA [1][2][3]. OA is a disease with multifactorial pathophysiology, including inflammatory processes, modulated by mediators, some of which ultimately accelerate cartilage degeneration [46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…OA is a disease with multifactorial pathophysiology, including inflammatory processes, modulated by mediators, some of which ultimately accelerate cartilage degeneration [46][47][48][49][50][51][52]. The infrapatellar fat pad, as the other intracapsular articular fat pads, consists mostly of adipocytes, but also contains various immune cells and mesenchymal stem cells, all of which are able to interact with other joint tissues, making it likely that inflammation of the infrapatellar fat pad may accelerate degenerative changes [1,2]. Less is known about the SPFP, but it may be assumed that pathophysiology is similar to that observed in the infrapatellar fat pad.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins have been detected in synovial fluid (SF) and the plasma of patients with OA [16][17][18]. A putative source of adipocytokine secretion in the region of the knee joint is the infrapatellar fat pad (IPFP) [19,20]. In addition, recent findings indicate that deteriorated articular cartilage is another source of adipocytokines within the joint [21].…”
Section: Introductionmentioning
confidence: 99%
“…It may also contribute to the inflammatory processes in patellofemoral knee pain, knee osteoarthritis, and rheumatoid arthritis [1]. The infrapatellar fat pad can influence pain sensation because nerve branches of many large lower extremity nerves run through it.…”
mentioning
confidence: 99%